2000
DOI: 10.2460/ajvr.2000.61.1512
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase expression in canine platelets and Madin-Darby canine kidney cells

Abstract: Detection of COX-1 by RT-PCR of RNA obtained from canine platelets is a novel finding. The 90% homology of the PCR product with the human sequence suggests strong conservation between the canine and human COX-1 gene. Cloning and sequencing of the canine gene will be required to fully characterize homologous regions. Because of the importance of COX in the inflammatory process and as a potential target of currently available nonsteroidal anti-inflammatory drugs (NSAID), a better understanding of canine COX may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…This study demonstrates COX‐2 expression in circulating canine platelets. Previously published studies were often unable to detect COX‐2 expression in circulating human and canine platelets . As in recently published human platelet studies, addition of a permeabilization step before flow cytometry enabled us to detect COX‐2 expression within the platelets of all of the dogs in this study.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This study demonstrates COX‐2 expression in circulating canine platelets. Previously published studies were often unable to detect COX‐2 expression in circulating human and canine platelets . As in recently published human platelet studies, addition of a permeabilization step before flow cytometry enabled us to detect COX‐2 expression within the platelets of all of the dogs in this study.…”
Section: Discussionmentioning
confidence: 66%
“…Relative to COX‐1, COX‐2 has a far more limited tissue distribution, and expression is often at much lower levels. COX‐2 expression occurs in the brain, kidney, thymus, and the vascular endothelium . COX‐2 is also present in circulating monocytes, tissue macrophages, and fibroblasts .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that RPF and GFR fell within the reference ranges and that there was no elevation of the NAG and GGT indices in healthy dogs treated with a reduced dosage of ketoprofen alone [31]. Kay-Mugford et al reported that MadinDarby canine kidney cells expressed both COX-1 and COX-2 [21]. Furthermore, COX-2 is sparsely expressed in the macula densa of the normal dog kidney, and up-regulation of COX-2 in the kidney and the stomach [16] has also been reported by several studies in dogs with volume or salt depletion; these results suggest that COX-2 and COX-1 have a possible role in the response that helps maintain renal function [3,22,40].…”
Section: Disccusionmentioning
confidence: 99%
“…We have previously reported that the long-term administration of ketoprofen (0.25 mg/kg and 1.0 mg/kg) has no effect on bleeding times in dogs [30,31], and Frenso et al reported that the shortterm use of meloxicam caused no significant changes in dog hemostatic variables [11]. Platelets are the only cells that exclusively express COX-1 in dogs [21]. COX-1 forms thromboxane A 2 , which in turn produces primary platelet plugs, through endogenous arachidonic acid that is supplied by phospholipase A 2 .…”
Section: Disccusionmentioning
confidence: 99%